2016
DOI: 10.2141/jpsa.0160015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Formic Acid-Treated Shrimp Meal on Growth Performance and Nutrient Digestibility in Broilers

Abstract: This study was conducted to know the effect of formic acid-treated shrimp meal as a protein source on growth performance, digestibilities, and nitrogen (N) retention for broilers. Shrimp meal (SM) was treated with 3% formic acid (w/v) at room temperature for 20 minutes, sun-dried, ground through a 1.0 mm mesh screen, and then ready to use as the treated SM (TSM). Forty-two male broiler chicks (8 d old, Ross 308) were randomly divided into 7 dietary groups (6 birds each), namely control diet, diets containing 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Several studies have demonstrated the benefits of silage prepared with the addition of organic acids in the diet, such as Widjastuti, Lengkey, Wiradimadja and Herianti (2011) who observed better results in birds fed diets containing 4% silage made with the addition of 3% formic and propionic acids (1: 1), and Rahman and Koh (2016) concluded that shrimp meal treated with 3% formic acid provided better digestibility of nutrients in broiler diets.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the benefits of silage prepared with the addition of organic acids in the diet, such as Widjastuti, Lengkey, Wiradimadja and Herianti (2011) who observed better results in birds fed diets containing 4% silage made with the addition of 3% formic and propionic acids (1: 1), and Rahman and Koh (2016) concluded that shrimp meal treated with 3% formic acid provided better digestibility of nutrients in broiler diets.…”
Section: Resultsmentioning
confidence: 99%
“…Yamamoto et al (2007) reported that freshwater fish silage has high fat content and digestibility due to its lipid composition, allowing its easy absorption by sheep. Several studies (Widjastuti et al, 2011;Rahman and Koh, 2016;Batalha et al, 2017) reported that the inclusion of fish silage in poultry diets provided high dietary nutrient digestibility.…”
Section: Digestibility and Physicochemical Characteristics Of Tambaqumentioning
confidence: 99%
“…Previous research on the utilisation of SWM has focused on broilers (Rahman and Koh 2016;Rahman, 2016), growing pullets (Islam et al, 2020), and pigs (Yugandharkumar et al, 2017). However, to the best of our knowledge, there is paucity of information on utilisation of SWM in rations for turkeys.…”
Section: Introductionmentioning
confidence: 99%